Theoretical and Experimental Heat Transfer in Solid Propellant Rocket Engine - Vicentin,Izabel Cecilia Ferreira de Souza (2019)
ABSTRACT: Accurate determination of heat flux is an important task not only in the designing aspect, but also in the performance analysis of rocket engines. In this purpose, this work deals with the heat flux determination in a combustion chamber through the inverse method. In this approach, the transient heat flux is determined from the experimental temperature data measured at the outer sidewall of the rocket engine. In this work the physical phenomenon was modeled by the transient one-dimensional heat equation in cylindrical coordinates and the material properties of the chamber were considered constant. Furthermore, the model is solved using the inverse heat conduction problem with least squares modified by the addition of Tikhonov regularization term of zero-order. Moreover, the sensitivity coefficients were obtained by Duhamel’s theorem. Through the regularization parameter, it was able to generate acceptable results even when using data with considerable experimental errors.